A cross‐sectional multisite exploration of Italian paediatric nurses' reported burnout and its relationship to perceptions of clinical safety and adverse events using the RN4CAST@IT‐Ped. (11th May 2020) - Bagnasco, Annamaria; Dasso, Nicoletta; Rossi, Silvia; Timmins, Fiona; Watson, Roger; Aleo, Giuseppe; Catania, Gianluca; Zanini, Milko; Sasso, Loredana
Abstract: Aim: To explore Italian paediatric nurses' reported burnout and its relationship to their perceptions of safety and adverse events. Design: A cross‐sectional study using the RN4CAST@IT‐Ped database with a web‐based survey design. Methods: The RN4CAST@IT‐Ped questionnaire was used to collect data in 2017. This comprised three main components: three dimensions (22 items) of the Maslach Burnout Inventory including emotional exhaustion, depersonalization and personal accomplishment. Participants also scored an overall grade of patient safety and estimated the occurrence of adverse clinical events. Results: Nurses ( N = 2, 243) reported high levels of burnout. Most rated clinical safety as high. The risk of adverse events ranged from 1.3–12.4%. The degree of burnout appeared to influence the perception of safety and adverse events. Conclusion: The association between nurses' burnout and perceptions of higher rates of adverse events and reduced safety in clinical practice is an important finding. However, it is unclear whether this was influenced by a negative state of mind, and whether reduced safety and increased adverse events negatively influenced nurses' well‐being, thus leading to burnout. Regardless, the association between nurses' burnout and these quality concepts needs further exploration to examine the effect, if any, on burnout and safety, and identify supportive mechanisms for nurses. Impact: The association between reported burnout and perception of safety and risk of adverse events in Italian paediatric nurses has been reported for the first time. Nurses reporting burnout are at greater risk of intensely negative perceptions of clinical safety and adverse events. This is an important finding as perceptions can influence practice and behaviours. Quality measures in children's clinical environments need to go beyond obvious indicators to examine nurses' well‐being as this also influences quality and safety. Abstract : 目的: 探讨意大利儿科护士工作倦怠及其与安全性和不良事件感知的关系。 设计: 一项横向研究, 采用RN4CAST@IT‐Ped数据库, 且调查设计基于网络。 方法: 于2017年采用RN4CAST@IT‐Ped问卷来收集数据。 该问卷包括三个主要组成部分: 即马斯拉赫工作倦怠量表的三个维度(22个条目), 包括情绪衰竭、人格解体和个人成就感。参与者还对患者安全进行了总体评分, 并对不良临床事件的发生情况进行了估计。 结果: 护士( N =2, 243)表示工作倦怠程度很高。大多数认为临床安全性很高。不良事件的风险在1.3 12.4%不等。工作倦怠程度可能会对安全性和不良事件感知产生影响。 结论: 护士工作倦怠与临床实践中不良事件发生率高、安全性降低的感知之间存在关联, 这是一项重要发现。然而, 目前尚不清楚这是否受到消极心态的影响, 以及安全性降低和不良事件增加是否对护士的健康产生负面影响, 从而导致工作倦怠。无论如何, 仍需就护士工作倦怠与此类质量观念之间的关系展开进一步的研究, 以检验对工作倦怠和安全性的影响(如有), 并确定面向护士的支持性机制。 影响: 本项研究首次探讨了意大利儿科护士的工作倦怠与安全性和不良事件风险感知之间的关系。表示有工作倦怠的护士更容易对临床安全和不良事件产生极强的负面感知。这是一项重大的发现, 因为感知会影响实践和行为。儿童临床环境中的质量措施需超越明显的指标来检查护士的健康, 因为这也会对质量和安全产生影响。